Pengaruh manajemen sumber daya manusia ramah lingkungan terhadap perilaku green service dengan tanggung jawab sosial perusahaan sebagai pemediasi - Antika, Rani; Suryani, Tatik (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
Many companies are implementing Green Human Resource Management (GHRM) and Green Service Behavior to support sustainable development and meet customer expectations. By investigating how GHRM initiatives influence employees' engagement in environmentally friendly service behaviors and the mediating role of CSR, this research contributes to understanding how organizations can promote sustainability and meet stakeholder expectations. However, there needs to be more research in this area. This study aims to investigate the impact of GHRM on green service behavior (GSB) and explore the role of Corporate Social Responsibility (CSR) as a mediator of GHRM on GSB. The study involved 108 respondents from PT. BIMA and data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS 3.0 application. The results show that GHRM can positively influence GSB, and CSR mediates this relationship.